2015
DOI: 10.1098/rspb.2015.1483
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent effects of cold and hyperkalaemia cause insect chilling injury

Abstract: Chilling injury and death are the ultimate consequence of low temperature exposure for chill susceptible insects, and low temperature tolerance is considered one of the most important factors determining insect distribution patterns. The physiological mechanisms that cause chilling injury are unknown, but chronic cold exposure that causes injury is consistently associated with elevated extracellular [ balance is critical to insect low temperature survival, and highlight novel routes of study in the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 50 publications
2
96
0
Order By: Relevance
“…S1). Further studies are needed to investigate these sources of variation, but here we clearly demonstrate a relationship between in vitro cell viability and polarization that reinforces the hypothesized model in which depolarization initiates an apoptotic/necrotic cascade (Hochachka, 1986;Boutilier, 2001;MacMillan et al, 2015c;Overgaard and MacMillan, 2017). These results also raise three important questions: (1) why might the V m of cold-acclimated cells be less affected by hyperkalemia?…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stresssupporting
confidence: 46%
See 3 more Smart Citations
“…S1). Further studies are needed to investigate these sources of variation, but here we clearly demonstrate a relationship between in vitro cell viability and polarization that reinforces the hypothesized model in which depolarization initiates an apoptotic/necrotic cascade (Hochachka, 1986;Boutilier, 2001;MacMillan et al, 2015c;Overgaard and MacMillan, 2017). These results also raise three important questions: (1) why might the V m of cold-acclimated cells be less affected by hyperkalemia?…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stresssupporting
confidence: 46%
“…Consistent with this idea we found that cold-acclimated locusts maintained polarization of V m better, and the same animals also showed improved cellular and organismal survival. In a previous study by MacMillan et al (2015c) we showed that only the combined effect of hyperkalemia and chilling causes injury, which suggested that V m must be depolarized past a critical threshold level to induce necrotic/apoptotic events. Our results support the hypothesis that by maintaining low hemolymph [K + ] during cold stress, cold-acclimated locusts better preserve V m , which ensures that cellular viability and organismal performance is maintained during chilling.…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Following an intense cold exposure (longer duration 56 and/or lower temperature), chill-susceptible insects acquire irreversible injuries and eventually 57 die (Koštál et al, 2004;Koštál et al, 2006;Rojas and Leopold, 1996) and rates of survival 58 following chilling are also regularly used as a measure of insect cold tolerance (Andersen et al,59 2015; MacMillan et al, 2015a; Sinclair et al, 2015). While there is often a high degree of 60 covariance in these three metrics, the mechanisms that underlie each of them is different and 61 in hemolymph water content (Koštál et induced hyperkalemia further depolarizes resting membrane potential by reducing the K + 107 gradient necessary for passive K + leak, and it is these cumulative short-and long-term 108 depolarizations that has been linked to cellular damage in locusts (MacMillan et al, 2015c). 109…”
Section: Chill Susceptibility In Insects 45mentioning
confidence: 99%